PENGARUH KEPEMILIKAN DAN KEPEMIMPINAN KELUARGA SERTA EFEKTIFITAS PENGAWASAN DEKOM TERHADAP KUALITAS AUDIT - Vera Diyanty; Eliza Fatima; Akhmad Syahroza (EKUITAS (Jurnal Ekonomi dan Keuangan), 2018)
This study aims to investigate the effect of family ownership, family leadership, and the monitoring role of the Board of Commissioners on the audit quality. This study uses a sample of non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2010 to 2013. Family ownership is measured through the ultimate ownership of the company. To determine whether the company's CEO is the founder of the company, family relationship data is used on all of the company's ultimate owners. The monitoring role of the Board of Commissioners is calculated through the Asean Corporate Governance Scorecard index. Data of auditor is obtained from Center for Supervision of Financial Service (P2PK). The results showed that family ownership either through direct or indirect mechanisms tend to choose Big 4 KAP than non Big 4. While Chief Financial Officer (CFOs) from family and corporate founders tend to choose Big 4 in auditing the company. This is done to maintain the company's reputation. The results also show that the effective monitoring of the Board of Commisionners (BOC) tends to choose Big 4 auditors compared to non Big 4.